Establishing ROS on Humanoid Soccer Robot-BarelangFC Software System - Susanto Susanto; Eko Priono; Riska Analia (JURNAL INTEGRASI, 2021)
Humanoid robot is built on several sub-programs or systems which is integrated to each main programs in order to command the robot to move as a soccer player. Each main programs namely as a movement system, a visual sense system (vision), a sub-controller system, and a game strategy. Currently, each of main system constructed using different programming language, for instance: the vision system used python while the others used C and LUA for the movement kinematics. Employing different programming language will affect to response system because each of main system need to be integrated using socket in the beginning process. Robot response will be slow and cost a lot of memory usage. Therefore, in this paper will present a migrating process into robot operating system (ROS) and switch all the robot main system into python language. The integrated program will be examined in real-time application while the robot moved on the field. We used a python ROS in order to make the robot play autonomously on the field.